Ipomea aquatica crude extract inhibits lipoxygenase, hyaluronidase and xanthine oxidase activities / Muhammad Helmi Nadri... [et al.] - Nadri, Muhammad Helmi; Cheng, Kian-Kai; Ong, Pei Ying; L., HongYeng; Othman, Nor Zalina; A. Mohd Yunos, A. Rafidah; Musa, Nur Fashya; Abdul Latiff, Norliza; Embi, Khairunnisa (Universiti Teknologi MARA, Negeri Sembilan, 2020)
Ipomea aquatica, locally known as water spinach, is one of the most common vegetable consumed by Malaysian. Based on previous studies, crude extract and phenolic compounds of I. aquatica exhibited several biological activities including antioxidant, anti-microbial and anti-proliferative. The presence of phenolic compounds in I. aquatica may contributed to their ability to inhibit enzymes, chelate metals and scavenge free radicals. Currently, no study reported on anti-inflammatory activity of I. aquatica with respect to lipoxygenase, hyaluronidase and xanthine oxidase enzymes. The present study aims to enhance current knowledge on biological properties of I. aquatica crude extract particularly on anti-inflammatory activity. Three enzymes that involve in inflammatory pathway were selected in this study including lipoxygenase, hyaluronidase and xanthine oxidase. I. aquatica was extracted in methanol and tested for lipoxygenase, hyaluronidase and xanthine oxidase at different concentrations using direct enzyme inhibition assay. Lipoxygenase, hyaluronidase and xanthine oxidase inhibitory activities of the methanol crude extract increased with increasing concentration. Highest inhibition activity against lipoxygenase, hyaluronidase and xanthine oxidase were observed at a concentration of 1000 μg/ml with inhibition of 87.18%, 95.36% and 78.38%, respectively. Our finding in this study indicates potential anti-inflammatory activity of I. aquatica crude extract through inhibition of lipoxygenase, hyaluronidase and xanthine oxidase.